A long fiber-reinforced laminated polytetrafluoroethylene gasket, its production method and use

CN122956748APending Publication Date: 2026-10-23NINGBO IDT SINYUAN SEALING TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611380294.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,在长期高温、高压及强碱性腐蚀环境的耦合作用下,现有改性四氟垫片的抗蠕变性能往往难以满足长周期稳定运行的需求,已成为制约电解槽系统整体寿命与密封安全的关键瓶颈

Benefits of technology

(1)本发明的长纤增强层叠式聚四氟乙烯垫片采用多层差异化设计的层叠结构,各层所用材料均为可熔融聚四氟乙烯(PFA)改性的聚四氟乙烯(PTFE)基体,再经过浸渍、破乳、压延成型、堆叠复合、高温烧结等工艺一体化成型,层间界面不使用胶黏剂,而是通过高温分子扩散形成牢固结合;该垫片应力松弛率(22hr@100℃)≤50%,拉伸强度≥20MPa,泄漏率≤3.0×10-4ml/s,显著优于市售改性四氟垫片;通过梯度结构设计与PFA改性基体的协同作用,解决了现有改性四氟垫片蠕变性能差、高填料含量导致脆化的技术难题,兼具低蠕变、高强度、优异绝缘性,可满足碱性水电解制氢电解槽的严苛密封要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956748A_ABST
    Figure CN122956748A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polytetrafluoroethylene polymer materials, and particularly relates to a long-fiber reinforced laminated polytetrafluoroethylene gasket and a preparation method and application thereof. The long-fiber reinforced laminated polytetrafluoroethylene gasket of the application adopts a laminated structure of multi-layer differentiation design, and the materials used in each layer are all polytetrafluoroethylene (PTFE) matrices modified by meltable polytetrafluoroethylene (PFA), which are integrally formed through processes such as impregnation, demulsification, calendering, stacking and compounding, high-temperature sintering and the like. Through the synergistic effect of the multi-layer laminated compounding form and the PFA matrix modification, the gasket is endowed with good comprehensive performance, including low creep performance, good mechanical strength and excellent insulation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polytetrafluoroethylene polymer materials technology, specifically relating to a long fiber reinforced laminated polytetrafluoroethylene gasket, its preparation method, and its application. Background Technology

[0002] Against the backdrop of the global energy structure's accelerated transformation towards diversification and cleaner energy, hydrogen energy, as a core carrier for building a future low-carbon energy system, is ushering in a historic development opportunity. Among various hydrogen production technologies, alkaline water electrolysis has established itself as the absolute mainstream route in large-scale centralized hydrogen production scenarios due to its comprehensive advantages, including high technological maturity, wide commercial application, controllable life-cycle costs, long operating life, and large single-tank hydrogen production scale. It is steadily moving from the demonstration operation stage to a new era of full commercialization and large-scale development.

[0003] As the industrialization of alkaline water electrolysis for hydrogen production accelerates, the actual operating conditions of electrolyzer systems are becoming increasingly complex, posing more stringent challenges to the long-term reliability of core components, especially the fuel cell stack sealing system. Currently, modified polytetrafluoroethylene (PTFE) gaskets are the most widely used sealing material in alkaline water hydrogen production fuel cell stacks. However, under the combined effects of long-term high temperature, high pressure, and strong alkaline corrosion environments, the creep resistance of existing modified PTFE gaskets often fails to meet the requirements for long-term stable operation, becoming a key bottleneck restricting the overall lifespan and sealing safety of the electrolyzer system.

[0004] In theory, increasing the filler content can improve the creep resistance of PTFE vinyl materials to some extent. However, excessive filler content often leads to decreased material toughness and increased gasket brittleness, weakening its mechanical strength and potentially affecting the reliability and safety of the sealing structure, making it difficult to meet the comprehensive performance requirements in practical applications. How to improve creep resistance while simultaneously ensuring material strength and long-term reliability of the sealing structure, achieving the optimal balance of comprehensive performance, is a core challenge that urgently needs to be overcome in the research and development of sealing materials for alkaline electrolytic cells.

[0005] Therefore, there is an urgent need for a long-fiber reinforced laminated polytetrafluoroethylene gasket that achieves synergistic optimization in material composition and structural design. Through the organic combination of multi-layer differentiated functional zoning, PFA matrix modification, and adhesive-free thermal bonding process, the gasket's creep resistance, mechanical strength, and electrical insulation properties can be comprehensively improved, achieving a balanced and unified performance across multiple indicators. This effectively meets the long-term sealing requirements of alkaline water electrolyzers under harsh operating conditions. Summary of the Invention

[0006] The purpose of this invention is to provide a long-fiber reinforced laminated polytetrafluoroethylene (PTFE) gasket, its preparation method, and its application. The preparation method of the long-fiber reinforced laminated PTFE gasket of this invention includes the following steps: S1, mixing PFA emulsion and PTFE emulsion to obtain a modified PTFE emulsion; S2, pretreating glass fiber cloth with a silane coupling agent to obtain a pretreated glass fiber cloth, and impregnating the pretreated glass fiber cloth with the modified PTFE emulsion obtained in step S1 to obtain a pre-impregnated PTFE glass fiber interlayer; S3, adding filler and the mixture from step S... S1. The modified PTFE emulsion is mixed and stirred evenly to obtain a mixture, which is then calendered to obtain a filler-modified PTFE layer; S4. The modified PTFE emulsion from step S1 is stirred and demulsified to obtain pure PTFE agglomerates, which are then molded to obtain a pure PTFE layer; S5. The pre-impregnated PTFE glass fiber interlayer from step S2, the filler-modified PTFE layer from step S3, and the pure PTFE layer from step S4 are composited to obtain a long-fiber reinforced laminated PTFE gasket. This invention, through multi-layer laminated composite and the synergistic effect of PFA matrix modification, endows the gasket with excellent comprehensive properties, including low creep performance, good mechanical strength, and excellent insulation performance.

[0007] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket, comprising the following steps: S1. Stir and mix the PFA emulsion and PTFE emulsion to obtain the modified PTFE emulsion; S2. Pre-treat the fiberglass cloth with a silane coupling agent to obtain a pre-treated fiberglass cloth. Impregnate the pre-treated fiberglass cloth with the modified PTFE emulsion described in step S1 to obtain a pre-impregnated PTFE fiberglass interlayer. S3. Mix the filler and the modified PTFE emulsion described in step S1 until they are homogeneous to obtain a mixture. Then, calender the mixture to obtain a filler-modified polytetrafluoroethylene layer. S4. Stir and break the emulsion of the modified PTFE emulsion described in step S1 to obtain pure PTFE agglomerates, and then perform molding treatment to obtain a pure polytetrafluoroethylene layer. S5. The pre-impregnated PTFE fiberglass interlayer described in step S2, the filler-modified PTFE layer described in step S3, and the pure PTFE layer described in step S4 are composited to obtain a long fiber reinforced laminated PTFE gasket.

[0008] As a preferred embodiment, the mass ratio of PFA emulsion to PTFE emulsion in step S1 is (5~50):100, and more preferably (40~50):100.

[0009] This invention uses PFA-modified PTFE as the base material for gaskets, ensuring effective protection of creep performance and tensile strength from the base layer. The introduction of PFA gives PTFE certain melt processing characteristics, which is beneficial to molecular diffusion and bonding at the interlayer interface.

[0010] As a preferred embodiment, the stirring and mixing conditions in step S1 are: a rotation speed of 40~50 r / min and a time of 50~60 min.

[0011] As a preferred embodiment, the calendering step in step S3 is as follows: the mixture is stirred and demulsified at 60~90℃ to obtain filler-modified PTFE agglomerates, and then the modified PTFE agglomerates are transferred to a calender and rolled into sheets, and then placed in a 200℃ oven for degreasing for 1~3 hours.

[0012] As a preferred embodiment, the conditions for stirring and demulsifying in step S4 are: stirring temperature of 60~90℃, stirring speed of 80~100r / min, and stirring time of 30~40min.

[0013] As a preferred embodiment, the molding process in step S4 is as follows: the pure PTFE agglomerates are placed in a calender and repeatedly calendered into sheets, and then placed in a 200°C oven for degreasing for 1-3 hours.

[0014] As a preferred embodiment, the composite treatment step S5 is as follows: the pre-impregnated PTFE glass fiber interlayer described in step S2, the filler-modified PTFE layer described in step S3, and the pure PTFE layer described in step S4 are stacked and placed in a calender for calendering at a temperature of 180~190℃, and then transferred to a sintering furnace for sintering at 370~390℃ for 2~4 hours.

[0015] This invention employs an adhesive-free thermal lamination process, which uses high-temperature sintering to allow molecular diffusion between layers to form a strong bond. This avoids the impurities, weak interfacial areas, and long-term aging problems introduced by traditional adhesives. Combined with precisely controlled process parameter windows, it ensures the stability and reproducibility of product performance.

[0016] As a preferred embodiment, the long-fiber reinforced laminated polytetrafluoroethylene gasket comprises, in sequence, a first pure polytetrafluoroethylene layer, a first filler-modified polytetrafluoroethylene layer, a pre-impregnated PTFE glass fiber intermediate layer, a second filler-modified polytetrafluoroethylene layer, and a second pure polytetrafluoroethylene layer.

[0017] As a preferred embodiment, the thickness of the first pure polytetrafluoroethylene layer and the second pure polytetrafluoroethylene layer is 0.1~0.2 mm.

[0018] As a preferred embodiment, the thickness of the first filler-modified polytetrafluoroethylene layer and the second filler-modified polytetrafluoroethylene layer is 0.3~0.8 mm.

[0019] As a preferred embodiment, the thickness of the pre-impregnated PTFE fiberglass interlayer is 0.3~2.0 mm.

[0020] The long-fiber reinforced laminated polytetrafluoroethylene gaskets of the present invention all use modified PTFE emulsion obtained by mixing PFA emulsion and PTFE emulsion. At the same time, each layer is integrally formed by pre-impregnation, calendering and high-temperature sintering processes. The interlayer interface does not use adhesives for bonding, but forms a strong bond through high-temperature molecular diffusion. The adhesive-free thermal bonding process ensures that the interface forms a strong bond through molecular diffusion, avoiding the limitation of application scenarios caused by the introduction of adhesives.

[0021] As a preferred embodiment, the long-fiber reinforced laminated PTFE gasket has a stress relaxation rate (22hr@100℃) ≤50%, tensile strength ≥20MPa, and leakage rate ≤3.0×10⁻⁶. -4 ml / s.

[0022] The long-fiber reinforced laminated polytetrafluoroethylene gasket of the present invention comprises a pure polytetrafluoroethylene layer, a filler-modified polytetrafluoroethylene layer, and a pre-impregnated PTFE glass fiber intermediate layer. The pure polytetrafluoroethylene layer mainly provides insulation, anti-sticking, and lubrication. The filler-modified polytetrafluoroethylene layer improves creep performance through gradient filler distribution. The pre-impregnated PTFE glass fiber intermediate layer provides structural reinforcement, giving the product good tensile strength and creep performance. The multi-layer composite structure maintains high tensile strength, avoids embrittlement problems caused by high filler content, significantly reduces stress relaxation rate, and improves long-term sealing reliability.

[0023] As a preferred embodiment, the pretreatment step in step S2 is as follows: by weight, 40-50 parts of silane coupling agent KH-550 are added to a mixture of 400-450 parts of anhydrous ethanol and 50-100 parts of deionized water, the pH is adjusted to 5-6 and stirred for 60-80 minutes to obtain a modified solution, and then a fiberglass cloth with a thickness of 0.1-0.2 mm is immersed in the modified solution for 30-40 minutes, filtered, washed with anhydrous ethanol, and dried to obtain the pretreated fiberglass cloth.

[0024] As a preferred embodiment, the pre-immersion treatment step S2 is as follows: immerse for 30~90s, remove, drain, and place in an oven to dry at 200℃ for 1~3h.

[0025] As a preferred embodiment, the filler in step S3 is selected from one or more of silicon dioxide, barium sulfate, alumina, silicon carbide, glass fiber powder, and carbon fiber powder.

[0026] As a preferred embodiment, the mass ratio of the filler to the modified PTFE emulsion is (5~40):100.

[0027] As a preferred embodiment, the filler is silicon dioxide and barium sulfate; the mass ratio of silicon dioxide to barium sulfate in the filler is (1~2):1.

[0028] As a preferred embodiment, the silica is perfluorinated modified nano-silica.

[0029] As a preferred embodiment, the barium sulfate is silica-alumina coated barium sulfate powder with a whiteness ≥98%, a pH of 7.5~8.5, and a volatile content ≤0.6% at 105℃.

[0030] The filler of this invention is selected from silica, barium sulfate, alumina, silicon carbide, glass fiber powder, and carbon fiber powder. It is preferred to use perfluorinated modified nano silica and silica-alumina coated barium sulfate in combination. By controlling the mass ratio of the two, a good synergistic effect is achieved, which maintains the high tensile strength of the gasket and significantly reduces the stress relaxation rate.

[0031] In the composite filler used in this invention, micron-sized silicon-aluminum coated barium sulfate forms the macroscopic framework, while nano-sized perfluorinated SiO2 fills the gaps between micron-sized particles and the amorphous regions of PTFE molecular chains. The former provides rigid framework support, and together with the latter, constructs an anti-creep physical network. Through multi-level particle size stacking, the structure is densified, thereby reducing the stress relaxation rate of the gasket and improving its overall strength.

[0032] In a second aspect, the present invention provides a long-fiber reinforced laminated polytetrafluoroethylene gasket prepared by the preparation method described in the first aspect.

[0033] Thirdly, the present invention provides an application of a long-fiber reinforced laminated polytetrafluoroethylene gasket prepared by the preparation method described in the first aspect in the sealing of an alkaline water electrolysis hydrogen production electrolyzer. The gasket is suitable for fuel cell stack sealing in large-scale centralized hydrogen production scenarios, with an operating temperature ≤100℃.

[0034] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: (1) The long-fiber reinforced laminated polytetrafluoroethylene gasket of the present invention adopts a multi-layered, differentiated laminated structure. The material used for each layer is a polytetrafluoroethylene (PTFE) matrix modified with meltable polytetrafluoroethylene (PFA). It is then integrally formed through processes such as impregnation, demulsification, calendering, stacking and lamination, and high-temperature sintering. No adhesive is used at the interlayer interface; instead, a strong bond is formed through high-temperature molecular diffusion. The stress relaxation rate (22hr@100℃) of this gasket is ≤50%, the tensile strength is ≥20MPa, and the leakage rate is ≤3.0×10 -4The speed of the modified PTFE gasket is significantly better than that of commercially available modified PTFE gaskets. Through the synergistic effect of gradient structure design and PFA modified matrix, the technical problems of poor creep performance and embrittlement caused by high filler content of existing modified PTFE gaskets are solved. It has low creep, high strength and excellent insulation properties, which can meet the stringent sealing requirements of alkaline water electrolysis hydrogen production electrolyzers.

[0035] (2) The layered design of the present invention achieves precise functional zoning: the outer pure polytetrafluoroethylene layer ensures insulation and surface properties, the filler-modified polytetrafluoroethylene layer improves creep performance, and the pre-impregnated PTFE glass fiber intermediate layer provides structural support, overcoming the limitations of single formulation or simple filler modification; the present invention endows the gasket with good comprehensive performance through the multi-layered composite form and the synergistic effect of PFA matrix modification, including low creep performance, good mechanical strength and excellent insulation performance. Attached Figure Description

[0036] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below.

[0037] Figure 1 This is a schematic diagram of the structure of the long fiber reinforced laminated polytetrafluoroethylene gasket of Embodiment 1 of the present invention.

[0038] Figure 2 This is a SEM image of the long-fiber reinforced laminated polytetrafluoroethylene gasket of Embodiment 1 of the present invention. Detailed Implementation

[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] The sources of some components in the examples and comparative examples are as follows: PFA emulsion, meltable polytetrafluoroethylene emulsion, model FC-680, purchased from Hangzhou Jingfu Technology Co., Ltd. PTFE emulsion, conventional polytetrafluoroethylene emulsion, model 4DC-A1, purchased from Hangzhou Jingfu Technology Co., Ltd. Fiberglass cloth, model GF200-7628, purchased from Zhenjiang Anzhidun High Temperature Fiber Products Co., Ltd. Silane coupling agent KH-550 was purchased from Nanjing Jingtianwei Chemical Co., Ltd. Nano silica, item number S104596, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Perfluorinated modified nano-silica was purchased from Quzhou Dongye Chemical Technology Co., Ltd. The silica-aluminum coated barium sulfate, model AY-JB54, has a whiteness of 98.5%, a pH of 8, and a volatile content of 0.5% at 105℃. It was purchased from Foshan Anyi Nanomaterials Co., Ltd.

[0041] Example 1 This embodiment provides a method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket, including the following steps: S1. Mix PFA emulsion and PTFE emulsion at a mass ratio of 50:100 at a speed of 40 r / min for 60 min to obtain modified PTFE emulsion. S2. By weight, 50 parts of silane coupling agent KH-550 are added to a mixture of 450 parts anhydrous ethanol and 50 parts deionized water. The pH is adjusted to 5 and the mixture is stirred for 80 minutes to obtain a modified solution. Then, a fiberglass cloth with a thickness of 0.2 mm is immersed in the modified solution for 30 minutes, filtered, washed with anhydrous ethanol, and dried to obtain a pretreated fiberglass cloth. The pretreated fiberglass cloth is then immersed in the modified PTFE emulsion described in step S1 for 60 seconds, removed and drained, and placed in an oven to dry at 200°C for 3 hours to obtain a pre-impregnated PTFE fiberglass interlayer. S3. Nano-silica (item number S104596) and modified PTFE emulsion with a mass ratio of 35:100 are mixed and stirred evenly to obtain a mixture. The mixture is placed at 90°C and stirred to break the emulsion to obtain filler-modified PTFE agglomerates. The modified PTFE agglomerates are then transferred to a calender and rolled into sheets. The sheets are then placed in a 200°C oven for degreasing for 3 hours to obtain a filler-modified polytetrafluoroethylene layer. S4. Stir and break the emulsion of the modified PTFE emulsion described in step S1 (stirring temperature is 90℃, stirring speed is 100r / min, stirring time is 30min) to obtain pure PTFE agglomerates. Place the pure PTFE agglomerates in a calender and repeatedly calender them into sheets. Then place them in a 200℃ oven for degreasing for 3h to obtain a pure polytetrafluoroethylene layer. S5. The pre-impregnated PTFE fiberglass interlayer described in step S2, the filler-modified PTFE layer described in step S3, and the pure PTFE layer described in step S4 are stacked and placed in a calender at 190°C for calendering and compounding. Then, they are transferred to a sintering furnace and sintered at 390°C for 2 hours to obtain a long-fiber reinforced laminated PTFE gasket. The long-fiber reinforced laminated PTFE gasket comprises, in sequence, a first pure PTFE layer (0.2 mm thick), a first filler-modified PTFE layer (0.8 mm thick), a pre-impregnated PTFE fiberglass interlayer (2.0 mm thick), a second filler-modified PTFE layer (0.8 mm thick), and a second pure PTFE layer (0.2 mm thick). A schematic diagram of the product structure of the long-fiber reinforced laminated PTFE gasket is shown below. Figure 1 As shown, the scanning electron microscope microscopic analysis is as follows: Figure 2 As shown.

[0042] Example 2 This embodiment provides a method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket, including the following steps: S1. Mix PFA emulsion and PTFE emulsion at a mass ratio of 40:100 at a speed of 50 r / min for 50 min to obtain modified PTFE emulsion. S2. By weight, 40 parts of silane coupling agent KH-550 are added to a mixture of 400 parts of anhydrous ethanol and 100 parts of deionized water. The pH is adjusted to 6 and the mixture is stirred for 80 minutes to obtain a modified solution. Then, a fiberglass cloth with a thickness of 0.1 mm is immersed in the modified solution for 40 minutes, filtered, washed with anhydrous ethanol, and dried to obtain a pretreated fiberglass cloth. The pretreated fiberglass cloth is then immersed in the modified PTFE emulsion described in step S1 for 30 seconds, removed, drained, and placed in an oven to dry at 200°C for 1 hour to obtain a pre-impregnated PTFE fiberglass interlayer. S3. Nano-silica (item number S104596) and modified PTFE emulsion at a mass ratio of 5:100 are mixed and stirred evenly to obtain a mixture. The mixture is placed at 60°C and stirred to break the emulsion to obtain filler-modified PTFE agglomerates. The modified PTFE agglomerates are then transferred to a calender and rolled into sheets. The sheets are then placed in a 200°C oven for degreasing for 1 hour to obtain a filler-modified polytetrafluoroethylene layer. S4. Stir and break the emulsion of the modified PTFE emulsion described in step S1 (stirring temperature is 60℃, stirring speed is 80r / min, stirring time is 40min) to obtain pure PTFE agglomerates. Place the pure PTFE agglomerates in a calender and repeatedly calender them into sheets. Then place them in a 200℃ oven for degreasing for 1h to obtain a pure polytetrafluoroethylene layer. S5. The pre-impregnated PTFE fiberglass interlayer described in step S2, the filler-modified PTFE layer described in step S3, and the pure PTFE layer described in step S4 are stacked and placed in a calender at 180°C for calendering and compounding. Then, they are transferred to a sintering furnace and sintered at 370°C for 4 hours to obtain a long-fiber reinforced laminated PTFE gasket. The long-fiber reinforced laminated PTFE gasket includes a first pure PTFE layer (thickness 0.1 mm), a first filler-modified PTFE layer (thickness 0.3 mm), a pre-impregnated PTFE fiberglass interlayer (thickness 0.3 mm), a second filler-modified PTFE layer (thickness 0.3 mm), and a second pure PTFE layer (thickness 0.1 mm) stacked sequentially.

[0043] Example 3 This embodiment provides a method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket, including the following steps: S1. Mix PFA emulsion and PTFE emulsion at a mass ratio of 45:100 at a speed of 48 r / min for 56 min to obtain modified PTFE emulsion. S2. By weight, 44 parts of silane coupling agent KH-550 are added to a mixture of 420 parts of anhydrous ethanol and 80 parts of deionized water. The pH is adjusted to 5.5 and stirred for 70 minutes to obtain a modified solution. Then, a fiberglass cloth with a thickness of 0.15 mm is immersed in the modified solution for 35 minutes, filtered, washed with anhydrous ethanol, and dried to obtain a pretreated fiberglass cloth. The pretreated fiberglass cloth is immersed in the modified PTFE emulsion described in step S1 for 60 seconds, removed, drained, and placed in an oven to dry at 200°C for 2 hours to obtain a pre-impregnated PTFE fiberglass interlayer. S3. Nano silica (item number S104596) and modified PTFE emulsion with a mass ratio of 40:100 are mixed and stirred evenly to obtain a mixture. The mixture is placed at 70°C and stirred to break the emulsion to obtain filler-modified PTFE agglomerates. The modified PTFE agglomerates are then transferred to a calender and rolled into sheets. The sheets are then placed in a 200°C oven for degreasing for 2 hours to obtain a filler-modified polytetrafluoroethylene layer. S4. Stir and break the emulsion of the modified PTFE emulsion described in step S1 (stirring temperature is 70℃, stirring speed is 90r / min, stirring time is 35min) to obtain pure PTFE agglomerates. Place the pure PTFE agglomerates in a calender and repeatedly calender them into sheets. Then place them in a 200℃ oven for degreasing for 2h to obtain a pure polytetrafluoroethylene layer. S5. The pre-impregnated PTFE fiberglass interlayer described in step S2, the filler-modified PTFE layer described in step S3, and the pure PTFE layer described in step S4 are stacked and placed in a calender at 185°C for calendering and compounding. Then, they are transferred to a sintering furnace and sintered at 380°C for 3 hours to obtain a long-fiber reinforced laminated PTFE gasket. The long-fiber reinforced laminated PTFE gasket includes a first pure PTFE layer (thickness 0.15 mm), a first filler-modified PTFE layer (thickness 0.4 mm), a pre-impregnated PTFE fiberglass interlayer (thickness 0.9 mm), a second filler-modified PTFE layer (thickness 0.4 mm), and a second pure PTFE layer (thickness 0.15 mm) stacked sequentially.

[0044] Example 4 The difference between this comparative example and Example 1 is that the filler was changed to perfluorinated modified nano-silica and silica-alumina coated barium sulfate powder in a mass ratio of 1:1.

[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that no pure polytetrafluoroethylene layer and prepreg glass fiber interlayer are added; instead, a filler-modified polytetrafluoroethylene layer is used directly as a gasket.

[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that no pre-impregnated PTFE glass fiber interlayer is added, and a gasket is obtained by composite treatment of a filler-modified PTFE layer and a pure PTFE layer.

[0047] Comparative Example 3 is a commercially available SiO2 modified PTFE gasket, IDT Unifluor 7551 from Germany.

[0048] Comparative Example 4 is a commercially available BaSO4 modified PTFE gasket, IDT Unifluor 7553 from Germany.

[0049] Comparative Example 5 is a commercially available SiC modified PTFE gasket, Klinger's TopChem2000 series.

[0050] Performance testing (1) Stress relaxation test: The test shall be conducted in accordance with the requirements of GB / T 12621-2008 Stress relaxation test method for gaskets for pipe flanges.

[0051] (2) Tensile strength test: The test shall be conducted in accordance with the requirements of GB / T 20671.7-2006 Classification system and test methods for non-metallic gasket materials Part 7: Tensile strength test method for non-metallic gasket materials.

[0052] (3) Leakage rate test: The test shall be conducted in accordance with the requirements of GB / T 12385-2025 Test method for sealing performance of gaskets for pipe flanges.

[0053] Table 1 Performance Test Results

[0054] The long-fiber reinforced laminated polytetrafluoroethylene gasket of the present invention adopts a multi-layered, differentiated laminated structure. The material used for each layer is a melt-modified polytetrafluoroethylene (PFA)-based polytetrafluoroethylene (PTFE) matrix, which is then integrally formed through processes such as impregnation, demulsification, calendering, stacking, and high-temperature sintering. Through the multi-layered laminated composite form and the synergistic effect of PFA matrix modification, the present invention endows the gasket with good comprehensive performance, including low creep performance, good mechanical strength, and excellent insulation performance.

[0055] Compared to Example 1, the filler was changed to a 1:1 mass ratio of perfluorinated modified nano-silica and silica-alumina coated barium sulfate powder. Due to the synergistic effect of the composite filler, the stress relaxation rate of the gasket decreased and the tensile strength increased (Example 4). Compared to Example 1, without adding a pure PTFE layer and a pre-impregnated PTFE fiberglass interlayer, the filler-modified PTFE layer was used directly as the gasket. Lacking the combined effect of the pure PTFE layer and the pre-impregnated PTFE fiberglass interlayer, the stress relaxation rate of the gasket increased and the tensile strength decreased (Comparative Example 1). Compared to Example 1, without adding a pre-impregnated PTFE fiberglass interlayer... The gaskets were composited using a filler-modified PTFE layer and a pure PTFE layer, but lacked the composite effect of a pre-impregnated PTFE fiberglass interlayer. As a result, the stress relaxation rate of the gaskets increased and the tensile strength decreased (Comparative Example 2). Compared with Example 1, the commercially available SiO2-modified PTFE gaskets showed increased stress relaxation rate and decreased tensile strength (Comparative Example 3). Compared with Example 1, the commercially available BaSO4-modified PTFE gaskets showed increased stress relaxation rate and decreased tensile strength (Comparative Example 4). Compared with Example 1, the commercially available SiC-modified PTFE gaskets showed increased stress relaxation rate and decreased tensile strength (Comparative Example 5).

Claims

1. A method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket, characterized in that, Includes the following steps: S1. Stir and mix the PFA emulsion and PTFE emulsion to obtain the modified PTFE emulsion; S2. Pre-treat the fiberglass cloth with a silane coupling agent to obtain a pre-treated fiberglass cloth. Impregnate the pre-treated fiberglass cloth with the modified PTFE emulsion described in step S1 to obtain a pre-impregnated PTFE fiberglass interlayer. S3. Mix the filler and the modified PTFE emulsion described in step S1 until they are homogeneous to obtain a mixture. Then, calender the mixture to obtain a filler-modified polytetrafluoroethylene layer. S4. Stir and break the emulsion of the modified PTFE emulsion described in step S1 to obtain pure PTFE agglomerates, and then perform molding treatment to obtain a pure polytetrafluoroethylene layer. S5. The pre-impregnated PTFE fiberglass intermediate layer described in step S2, the filler-modified PTFE layer described in step S3, and the pure PTFE layer described in step S4 are composited to obtain a long fiber reinforced laminated PTFE gasket. The long-fiber reinforced laminated polytetrafluoroethylene gasket comprises, in sequence, a first pure polytetrafluoroethylene layer, a first filler-modified polytetrafluoroethylene layer, a pre-impregnated PTFE glass fiber intermediate layer, a second filler-modified polytetrafluoroethylene layer, and a second pure polytetrafluoroethylene layer.

2. The method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket according to claim 1, characterized in that, The thickness of the first pure polytetrafluoroethylene layer and the second pure polytetrafluoroethylene layer is 0.1~0.2mm; The thickness of the first filler-modified polytetrafluoroethylene layer and the second filler-modified polytetrafluoroethylene layer is 0.3~0.8mm; The thickness of the pre-impregnated PTFE fiberglass interlayer is 0.3~2.0 mm.

3. The method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket according to claim 1, characterized in that, The stress relaxation rate (22hr@100℃) of the long-fiber reinforced laminated PTFE gasket is ≤50%, the tensile strength is ≥20MPa, and the leakage rate is ≤3.0×10⁻⁶. -4 ml / s.

4. The method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket according to claim 1, characterized in that, The pretreatment step in step S2 is as follows: by weight, 40-50 parts of silane coupling agent KH-550 are added to a mixture of 400-450 parts of anhydrous ethanol and 50-100 parts of deionized water, the pH is adjusted to 5-6 and stirred for 60-80 minutes to obtain a modified solution, and then a fiberglass cloth with a thickness of 0.1-0.2 mm is immersed in the modified solution for 30-40 minutes, filtered, washed with anhydrous ethanol, and dried to obtain the pretreated fiberglass cloth.

5. The method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket according to claim 1, characterized in that, The pre-soaking process described in step S2 is as follows: soak for 30-90 seconds, remove, drain, and place in an oven to dry at 200°C for 1-3 hours.

6. The method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket according to claim 1, characterized in that, The filler mentioned in step S3 is selected from one or more of the following: silicon dioxide, barium sulfate, alumina, silicon carbide, glass fiber powder, and carbon fiber powder. The mass ratio of the filler to the modified PTFE emulsion is (5~40):

100.

7. The method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket according to claim 6, characterized in that, The filler is silicon dioxide and barium sulfate; the mass ratio of silicon dioxide to barium sulfate in the filler is (1~2):

1.

8. The method for preparing a long-fiber reinforced laminated polytetrafluoroethylene gasket according to claim 7, characterized in that, The silica is perfluorinated modified nano-silica; The barium sulfate is silica-alumina coated barium sulfate powder with a whiteness ≥98%, a pH of 7.5~8.5, and a volatile content ≤0.6% at 105℃.

9. A long-fiber reinforced laminated polytetrafluoroethylene gasket, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. The application of a long-fiber reinforced laminated polytetrafluoroethylene gasket prepared by the preparation method according to any one of claims 1 to 8 in the sealing of an alkaline water electrolysis hydrogen production electrolyzer, wherein the gasket is suitable for fuel cell stack sealing in large-scale centralized hydrogen production scenarios and has an operating temperature ≤100℃.